CaO oxide and hydroxide (Ca(OH)2) in the treatment of roughage - Oliveira, Gabriel Rodrigues Silva; Pires, Aureliano José Vieira; Mendes, Raiane Barbosa; Batista, Tainan da Silva (Brazilian Journal of Science, 2023)
The aim of this review was to compile information about the treatment of bulky foods with calcium oxides and hydroxides and their supply to ruminants. This treatment aims to improve the digestibility of roughage through alkaline hydrolysis, benefiting the nutritional value. Studies have been developed with the aim of improving the nutritional characteristics and reducing the frequency of cutting through the storage of sugarcane from its treatment with oxide (CaO) or calcium hydroxide (Ca(OH)2). However, these treatments are not always able to improve the composition of foods, especially in terms of fiber and digestibility. This way, forage treatment using calcium oxides and hydroxides is not recommended due to the lack of results that demonstrate improvement in forage quality, consumption characteristics and animal performance.